DNA marker-assisted selection to pyramid rust resistance genes in “carioca” seeded common bean lines - Carneiro, José Eustáquio S.; Moreira, Maurilio A.; Barros, Everaldo G.; Souza, Thiago Lívio P. O.; Ragagnin, Vilmar A.; Dessaune, Suelen N.; Sanglard, Demerson A. (Euphytica, 2014)
This work reports a gene pyramiding approach assisted by DNA markers used to develop “carioca” seeded common bean (Phaseolus vulgaris L.) elite lines harboring three different rust resistance genes. Rust is among the most destructive diseases that attack P. vulgaris and cause serious damage worldwide. The rust resistance genes Ur-5 (from ‘Mexico 309’), Ur-11 (from ‘BelMiDak RR-3’), and Ur-14 (from ‘BRS Pioneiro’, a “carioca” seeded cultivar derived from the resistance source ‘Ouro Negro’) were combined in the “carioca” seeded bean cultivar ‘Rudá’. Firstly, two different backcross programs were conducted separately to produce progenies harboring individually the Ur-5 and Ur-11 genes. Molecular fingerprinting analysis was used to select plants genetically similar to ‘Rudá’ in the backcross cycles to accelerate the recurrent-background recovery. The obtained progenies were initially intercrossed and then crossed with ‘BRSMG Pioneiro’ (Ur-14). The final F1 plants derived from these crosses were screened with DNA markers linked to the three rust resistance genes: SI19 (Ur-5), SAE19 (Ur-11) and OPX11 (Ur-14). The plants selected as harboring all the alleles of interest were used to obtain the next generations. The selection based on DNA markers was conducted up to the F4:5 generation. We were able to select F4:7 progenies showing all the DNA markers associated to the genes of interest and resistant to all specific races of U. appendiculatus used for phenotypically detecting each one of the rust resistance genes. Yield evaluations show that these selected lines are as productive as the recurrent parent ‘Rudá’ and high-performing control cultivars grown in Brazil.
Keywords: Disease resistance; Marker-assisted selection; Molecular markers; Phaseolus vulgaris; Plant breeding; Uromyces appendiculatus